WORKDISCIPLINE ANDPEDAGOGIC COMPETENCE TO TEACHERS OF YADIKAPRINGSEWU VOCATIONAL PERFORMANCE - Dwi Ana Hastuti (Proceeding International Conference on Information Technology and Business, 2018)
The problem in this study is the ability of teachers in the learning management of students is not optimal, lack of discipline of teachers in carrying out tasks and abilities and knowledge of teachers that are not in accordance with the competence and work discipline of teachers that are less optimal impact on the quality of graduates which means teacher performance in teaching not optimal yet. The purpose of this study was to determine the effect of work discipline and pedagogic competence together on the performance of teachers of SMK Yadika Pringsewu. This research is a descriptive analytical study, where the author describes the object of research and analyzes the data. Data processing and analysis methods use qualitative and quantitative analysis method. Qualitative analysis is used to describe the influence of work discipline and pedagogic competence together on the performance of teachers of SMK Yadika Pringsewu. The results showed that there was a positive and significant influence on work discipline on performance, there was a positive and significant influence on pedagogic competence on performance and there was a positive and significant influence on work discipline and pedagogical competence together on the performance of teachers of SMK Yadika Pringsewu.Keywords: Discipline, Pedagogic Competence, and Performance